"It's Not a Tumor": A Rare Case of Symptomatic Cerebellar Developmental Venous Anomaly. Issue 2 (February 2019) - Augenstein, Julie A.; Chapman, Teresa; McNeil, Michael J.; Lo, Mark D.
Abstract : Abstract: Cerebral developmental venous anomalies (DVAs) are benign anatomical variants of the venous system and are commonly described as an incidental finding without clinical significance. Neurologic symptoms or abnormal examination findings are rare and usually attributed to hemorrhagic complications related to coexisting cavernous malformations. There have been limited case reports of symptomatic, uncomplicated DVAs described in the literature. The following case describes a previously healthy child who presented to the emergency department with an acute onset of altered mental status, headache, and focal neurologic examination abnormalities. Magnetic resonance imaging revealed a prominent cerebellar DVA. There was no evidence of a cavernous angioma, hemorrhage, or acute parenchymal injury. This case report illustrates a clinically symptomatic, uncomplicated posterior fossa DVA. It provides additional evidence regarding the potential for a cerebral venous malformation in causing focal neurologic deficits.